Developing Organisational Resilience to Fundamental Crisis: Evaluating the role of Social Media as a Key Enabler of Bricolage within Retail SME’s. - Dafydd Cotterell (Institute of Small Business and Entrepreneurship (ISBE), 27-28 October 2022, York, UK., 2022)
Recent years have offered the UK economy an unprecedented series of fundamental crisis events fostering complex challenges for UK businesses. These crisis events – namely Brexit, Covid-19 and the Ukraine War – continue to test the adaptive capacity of businesses and have impeded the continuity of trade within a number of UK sectors. Such crises events have had particularly sobering effects for the UK retail sector, where businesses have seen turbulence in their supply chains in addition to facing legal restrictions around trade as a result of Covid-19. Academic studies within the areas of Business Continuity Management, Crisis Management and Organisational Resilience are highly mimetic and increasingly isomorphic were little has been achieved in the development of meaningful theory within a small business context. This therefore indicates that academic knowledge of managing crisis is underdeveloped and needs extensive attention.Set within the context of Covid-19 specifically, this study evaluates the propensity of social media as a key enabler for resource bricolage within retail SME’s across England & Wales. Resource bricolage receives much precedent within entrepreneurship literature as an effective vector of organisational resilience in the face of crisis, however little is known regarding the key enablers of the bricolage process. With social media’s well documented ability to create positive commercial outcomes within business operations such as marketing, internationalisation and innovation, it is therefore logical to now evaluate its ability to create positive commercial outcomes in times of crisis.